2010
DOI: 10.1371/journal.pgen.1001181
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral Dystrophy: Incomplete Suppression of a Retrotransposed Gene

Abstract: Each unit of the D4Z4 macrosatellite repeat contains a retrotransposed gene encoding the DUX4 double-homeobox transcription factor. Facioscapulohumeral dystrophy (FSHD) is caused by deletion of a subset of the D4Z4 units in the subtelomeric region of chromosome 4. Although it has been reported that the deletion of D4Z4 units induces the pathological expression of DUX4 mRNA, the association of DUX4 mRNA expression with FSHD has not been rigorously investigated, nor has any human tissue been identified that norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
778
5
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 423 publications
(869 citation statements)
references
References 26 publications
43
778
5
5
Order By: Relevance
“…3,5,6 Furthermore, expression of this long form of DUX4 is detected in only a small percentage (B0.1%) of nuclei in cultures of FSHD subject-derived myogenic cells. 6 Data acquisition for our study was completed before publication of this disease model, so we did not include analyses of the long form of DUX4 here. In our study, we found that expression of a panel of genes, myotube formation, and stressor responses were, on average, indistinguishable between FSHD and unaffected cell cultures.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…3,5,6 Furthermore, expression of this long form of DUX4 is detected in only a small percentage (B0.1%) of nuclei in cultures of FSHD subject-derived myogenic cells. 6 Data acquisition for our study was completed before publication of this disease model, so we did not include analyses of the long form of DUX4 here. In our study, we found that expression of a panel of genes, myotube formation, and stressor responses were, on average, indistinguishable between FSHD and unaffected cell cultures.…”
Section: Discussionmentioning
confidence: 98%
“…6,[8][9][10][11][12][13][14][15] Some of these studies have suggested possible FSHD-specific phenotypes, including increased sensitivity to oxidative stress, 14,16 altered myotube morphology, 14 and altered expression of FRG1 18 or FRG2. 12 We found that proliferating and differentiating cultures of both FSHD and unaffected cells expressed similar patterns of FRG2 mRNA, and a recent study also found FRG2 mRNA in unaffected myoblasts and myotubes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Both forms are associated with partial chromatin relaxation of the D4Z4 macrosatellite repeat array on the subtelomere of the long arm of chromosome 4 and transcriptional derepression of the D4Z4 unit-encoded DUX4 retrogene in skeletal muscle. [5][6][7][8][9] DUX4 is a germ line transcription factor that is normally repressed in somatic cells. 7 Its expression in skeletal muscle activates genes involved in germ line and early stem cell development, as well as specific classes of repeat elements, and overexpression of DUX4 in somatic cells causes cell death.…”
Section: Introductionmentioning
confidence: 99%